PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA ELEMEN DESAIN BRIEF MATA PELAJARAN DESAIN KOMUNIKASI VISUAL - Elma Tesa; Heri Mulyono; Sofia Edriati (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
The problems that exist in desain comunication visual for elemen elemen desain brief are the absence of learning media that supports student learning outcomes, so students find it difficult to understand the material while studying. This study aims to produce valid and practical android-based learning media. This study uses the Research and Development (RD) method with the ADDIE development model. The subjects of this study amounted to 15 students as a sample. Data collection techniques using a questionnaire with a Likert scale. The results of this study indicate the average value of the media expert's validity test is 0.704 with a valid category and material expert is 0.73 with a valid category. For the practicality test, the teacher's response reached 87,5% with a very practical category and for the student response it reached 89,92% with a very practical category. Conclusions based on the assessment along with input from media experts and material experts as well as the results of field trials of android-based learning media have been tested for feasibility and can be used as learning media for elemen elemen desain brief.